PRACTICAL ASPECTS REGARDING THE CLAIM FOR THE ANNULMENT OF THE RESOLUTIONS OF THE GENERAL MEETING OF SHAREHOLDERS, FROM A SUBSTANTIAL AND PROCEDURAL PERSPECTIVE - Roxana - Mihaela CATEA (Challenges of the Knowledge Society)
The purpose of this paper is to provide a brief analysis of the legal framework regarding the procedural and substantial dispositions governing the claim for the annulment of the resolutions of the general meeting of shareholders. The main objective is to render a practical tool both to stakeholders and third parties who are interested in the legal means available for blocking the implementation of any measures which are contrary to the company’s interest. Further to the amendments brought through the New Civil Procedural Code, the claim for annulment of the resolutions of the general assembly must be analyzed from a procedural point of view, as well as from a substantial standpoint. The shareholders must be aware of the grounds for challenging a general assembly's resolution to properly safeguard their rights. One common issue which is invoked as grounds for annulment is the abuse of majority of the majority shareholder. However, the difficulty of alleging such a reason is left to practitioners. Therefore, its application, although not wide, is highly imaginative.